Notes on the identity and status of two Legumes (Fabaceae: Papilionoideae) from India - Krishnaraj, Moothedathu Venugopalan Nair; Mohanan, Narayanan Nair (Phytotaxa, 2012)
Indigofera karaiyarensis and Mucuna pruriens var. thekkadiensis are synonymized under Indigofera astragalina and Mucuna pruriens var. hirsuta respectively.